Optimal real-time tuning of autonomous distributed power systems using modern techniques - Chatterjee, Shamik; Mohammed, Ahmed Nura; Mishra, Sachin; Sharma, Naveen Kumar; Selim, Ali; Bajaj, Mohit; Rihan, Mahmoud; Kamel, Salah (Frontiers in Energy Research, 2023)
As a result of growing concern for environment, deregulation and security of supply; the future power system will prioritize distributed generation (DG), this necessitate secure, fully autonomous, reliable control and co-ordination among many number of distributed generation points. Therefore, DG has to be fine-tuned and synchronized effectively even on real time for improving resilience with control and coordination, so new techniques are required to keep up with the trail of these challenges. Consequently, in this work an autonomous fuel cell distributed power model is considered for systematic offline and online enquiry using a high performance proportional-integral-derivative-second order derivative (PIDD2) controller optimized with Moth flame optimization (MFO) technique and/or in synchronism with real time Sugeno fuzzy logic (SFL). The outstanding transients characteristics acquired for both offline and online operation under distinct perturbation and/or parameter specification transcend those offered by all other techniques in the recent literature of the model. Also robustness examination offline demonstrates further the strong performance of the technique to stochasticity, thus the technique is flexible enough to be used an effective tool for enhancing system with identical or similar specification.